A Chimeric Cationic Peptide Composed of Human β-Defensin 3 and Human β-Defensin 4 Exhibits Improved Antibacterial Activity and Salt Resistance - Yu, Wenjing; Ning, Nianzhi; Xue, Ying; Huang, Yanyu; Guo, Feng; Li, Tao; Yang, Boning; Luo, Deyan; Sun, Yakun; Li, Zhan; Wang, Jianxin; He, Zhili; et al. (Frontiers in Microbiology, 2021)
Human beta-defensins (hBDs) play an important role in the host defense against various microbes, showing different levels of antibacterial activity and salt resistance in vitro. It is of interest to investigate whether can chimeric hBD analogues enhanced antibacterial activity and salt resistance. In this study, we designed a chimeric human defensin, named H4, by combining sequences of human beta-defensin-3 (hBD-3) and human beta-defensin-4 (hBD-4), then evaluated its antibacterial activity, salt resistance and cytotoxic effects. The result showed that the antibacterial activity of H4 against most tested strains, including Klebsiella pneumonia, Enterococcus faecalis, Staphyloccocus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia, and Acinetobacter baumannii was significantly improved compared to that of hBD-3 and hBD-4. Notably, H4 exhibited significantly better antibacterial activity against multidrug resistant isolate Acinetobacter baumannii MDR-ZJ06 than commonly used antibiotics. Chimeric H4 still showed more than 80% antibacterial activity at high salt concentration (150 μM), which proves its good salt tolerance. The cytotoxic effect assay showed that the toxicity of H4 to Hela, Vero, A549 cells and erythrocytes at a low dose (<10 μg/ml) was similar to that of hBD-3 and hBD-4. In conclusion, given its broad spectrum of antibacterial activity and high salt resistance, chimeric H4 could serve as a promising template for new therapeutic antimicrobial agents.